2021
DOI: 10.3390/ijms22169037
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Malformations—Current Understanding of the Pathogenesis with Implications for Treatment

Abstract: Arteriovenous malformations are a vascular anomaly typically present at birth, characterized by an abnormal connection between an artery and a vein (bypassing the capillaries). These high flow lesions can vary in size and location. Therapeutic approaches are limited, and AVMs can cause significant morbidity and mortality. Here, we describe our current understanding of the pathogenesis of arteriovenous malformations based on preclinical and clinical findings. We discuss past and present accomplishments and chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 124 publications
0
40
0
5
Order By: Relevance
“…Abdominopelvic arteriovenous malformation (AVM) is an uncommon vascular lesion, for which the etiology is usually congenital, and the diagnosis and treatment are difficult. The AVM is characterized by abnormal connections between supplying arteries and draining veins ( 1 ). It may begin with an asymptomatic lesion, but often progresses over time and expands secondary to trauma or hormonal change, such as that during puberty or pregnancy ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abdominopelvic arteriovenous malformation (AVM) is an uncommon vascular lesion, for which the etiology is usually congenital, and the diagnosis and treatment are difficult. The AVM is characterized by abnormal connections between supplying arteries and draining veins ( 1 ). It may begin with an asymptomatic lesion, but often progresses over time and expands secondary to trauma or hormonal change, such as that during puberty or pregnancy ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such continued stimulation increases the risk of hemorrhage and bleeding, deteriorated flow can cause blood steal phenomena, and the circulation of high-flow blood creates a relatively hypoxic environment in the proximal tissues at the AVM site. Patients with AVM often have a high hemorrhage risk and may require several surgeries along with embolization and sclerotherapy [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vivo studies showed that any of the three HHT gene mutations could cause vascular malformations since knockout alleles for ENG, ACVRL1, and SMAD4 all result in HHT-like phenotypes in mice [1]. Mechanistically, in addition to the TGFß/BMP pathway, several other pathways, such as VEGF, mTOR, and PI3K/AKT signaling pathways, are associated with AVM formation and HHT pathogenesis [1]. Recently, pharmacologically combined treatment with Sirolimus and Nintedanib has been shown to correct Smad1/5/8 reduction and mTOR and VEGFR2 activation.…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary hemorrhagic telangiectasia (HHT), also known as Rendu-Osler-Weber syndrome, is a complex genetic disease that causes abnormalities of blood vessel formation in the liver, lung, brain, skin, nasal mucosa, and gastrointestinal tract [1]. HHT is a rare disease, affecting approximately 1 in 5000-10000 people worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation